Science Mapping of Perceived Organizational Support: A Bibliometric Analysis Approach - Pringgabayu, Dematria; Disman, Disman; Eeng Ahman (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2023)
The purpose of this study is to obtain related topic and information regarding perceived organizational support. In conducting this study, the researcher utilized Scopus database for data mining and extraction. A total of 816 articles were discovered in the Scopus database accessed on July, 2023. Afterward, VOSviewer is utilized for scientific mapping and analysis of publication performance such as identify the contributions of authors, journals, countries, and author keywords number. Several countries have contributed to publications of perceived organizational support. The data reveals that the US contributes the most to this publishing subject, followed by China, India, the UK, Australia, Malaysia, Pakistan, South Korea, Canada, and Turkey. Most works on the topic are from these nations. The